The Role of The Husband as A Companion in The Childbirth Process at The Bumiayu District Health Center, Brebes Regency - Maryam, Maryam; Abkar, Raden; Ismarwati, Ismarwati (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2021)
Background: This research is conducted to increase the husband's involvement in their active role as a companion from pregnancy until childbirth so that the psychology of the mother during the process becomes good and goes well. This research aims to understand the husband's role in their accessibility, engagement, responsibility, and couple relationship in line with their role as individual, family, community, society, and policy. Method: This research was qualitative study through in-depth interviews with five informant couples as primary sources and four supportive informants such as midwives or health workers in the area of Puskesmas (Primary Health Center) Bumiayu and Kaliwadas. They were interviewed separately in different places and times. Results: The husband's role during the process of childbirth covers their accessibility, which is his direct presence to accompany his wife, their engagement as physical and emotional involvement during the process, their responsibility towards his wife's needs, and couple relationship as his care and concern of his wife. Some factors that affect the role of the husband such as individual, family support (parents), community or closer environmental support such as workplaces that may grant permission or leave from work during the process; social support from midwife which involved of giving information, instruction, to them and her husband; and policy as stated in Regulation of the Minister of Health no. 97, 2014 article 12 verse 4(f) dan article 14, about husband policy (SIAGA) 1999-2000 and KIA book. Conclusion: The primary role of the husband during pregnancy and childbirth are accessibility and engagement. Some factors that affect their role are individual motivation, community or support of her closest environment, and society or the role of health workers in supporting a husband's responsibility. The Standard Operating Procedures about the role of the husband as a companion of his wife during pregnancy and childbirth period are not formulated yet.